Student Teachers' Conceptions of History. Issue 1 (1st December 2001) - Virta, Arja
This paper reports on the beliefs and conceptions of history that young adults have constructed on the basis of their history studies at school. The data consist of openended written responses of 92 first and second year university students (prospective primary school teachers) to the following questions: 1) Why do we study history at school? 2) What is the significance of history in society? 3) How do I understand the concept of history? 4) What does history mean to me? 5) What is my own place in history? The data were analysed qualitatively, and the method resembles the phenomenographic approach, trying to find out different aspects of meaning. This approach to young adults' beliefs of history is often ignored in school history, which emphasises transmission of factual content. For most respondents, the role of history was mainly cognitive, as an explanation to the contemporary world. Critical approach to history, and to controversial issues was less obvious, and very seldom the respondents made remarks on the relativity and fragility of historical information. Some of the students also made a distinction between history as a school subject, and history as a dimension of the worldview. One group of students underlined the emotional and entertaining function of history. Most respondents were obviously not used to thinking about the personal significance of history, but nevertheless, they were ready and willing to apply history as a tool of organising the world they live in.